2021
DOI: 10.1101/2021.06.21.449178
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial transcriptomic characterization of COVID-19 pneumonitis identifies immune circuits related to tissue injury

Abstract: Severe lung damage in COVID-19 is known to involve complex interactions between diverse populations of immune and stromal cells. In this study, we applied a spatial transcriptomics approach to better delineate the cells, pathways and genes responsible for promoting and perpetuating severe tissue pathology in COVID-19 pneumonitis. Guided by tissue histology and immunohistochemistry we performed a targeted sampling of dozens of regions representing a spectrum of diffuse alveolar damage from the post-mortem lung … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…We previously generated selective spatial transcriptomics from 46 areas of postmortem biopsies from patients with critical COVID-19 covering a spectrum of alveolar injury 64 . To explore the expression Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously generated selective spatial transcriptomics from 46 areas of postmortem biopsies from patients with critical COVID-19 covering a spectrum of alveolar injury 64 . To explore the expression Fig.…”
Section: Resultsmentioning
confidence: 99%
“…= 0.55 cm 2 ) for hematoxylin and eosin (H&E) analysis. Sections were analyzed by NanoString GeoMx Digital Spatial Profiling with normalization and downstream analysis by WGCNA 66 and cell deconvolution 65 as described previously 64 . For deconvolution with SpatialDecon in R v.1.0.0, cell profiles were obtained from the Human Cell Atlas healthy lung and scRNA-seq-appended with neutrophil data 105 using the R 'Lung_plus_neut' dataset.…”
Section: Facs Analysismentioning
confidence: 99%
“…Analysing inflammatory gene expression using genes from the molecular signature database (Liberzon et al, 2015) showed that FG-4592 had a modest effect on the lung inflammasome (Supplementary Fig.6) . Of note, expression of the viral entry receptors Ace2 and Tmprss2 were significantly downregulated (log 2 fold change of −1.45 and −1.52 respectively) in the infected tissue, likely reflecting viral cytopathology (Cross et al, 2021). Loss of ciliated epithelial cells is a key feature of COVID-19 resulting from damage to the airway epithelia (Pizzorno et al, 2020; Robinot et al, 2021; Zhu et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…6). Of note, expression of the viral entry receptors Ace2 and Tmprss2 were significantly downregulated (log 2 fold change of -1.45 and -1.52 respectively) in the infected tissue, likely reflecting viral cytopathology (Cross et al, 2021). Loss of ciliated epithelial cells is a key feature of COVID-19 resulting from damage to the airway epithelia (Pizzorno et al, 2020;Robinot et al, 2021;Zhu et al, 2020).…”
Section: Fg-4592 Reduces Ciliated Epithelial Damage In the Lungmentioning
confidence: 99%
See 1 more Smart Citation